(untitled) (SCHOOLAR: Social and Literature Study in Education, 2023)
The purpose of the study is to describe the implementation of online learning in the new normal era, as well as to solve problems and determine the most appropriate solution to the problems or difficulties faced by students in understanding mathematics courses in particular, for future provisions in managing life and preparing themselves as prospective educators. . This type of research is a case study research and the research method used in this research is a descriptive exploratory qualitative data method, namely digging up complete data from students who are used as research objects in accordance with this case study. Data collection techniques used in this study were interviews, observations, and questionnaires. The results of the research in the form of a diagnosis of learning difficulties which include data analysis from education and online learning can be used with consideration of paying attention to the condition of students, so that they will get used to adjusting to the online system, learning can be carried out properly.